Facile Synthesis of Nitrogen and Halogen Dual‐Doped Porous Graphene as an Advanced Performance Anode for Lithium‐Ion Batteries. Issue 5 (3rd January 2018) - Liu, Huanlong; Tang, Yufeng; Zhao, Wei; Ding, Wei; Xu, Jijian; Liang, Chenliang; Zhang, Zhichao; Lin, Tianquan; Huang, Fuqiang
Abstract: Nonmetal‐dual doped graphene has attracted considerable attention as high‐performance anode material for lithium‐ion batteries (LIBs) due to the synergistic effects of heteroatom dopants. Herein, nitrogen and halogen (including Cl, Br, and I) dual‐doped graphene is successfully synthesized by a general wet chemical method and lithium storage performance of N, Cl codoped graphene as anode material for LIBs is investigated in detail. The dual‐doped heteroatoms introduce abundant defects and expand the interlayer spacing of graphene to benefit lithium insertion and extraction. When used as a typical anode material, the N and Cl dual‐doped porous graphene reveals a high specific capacity of 1200 mA h g −1 at 0.1 A g −1 and 1010 mA h g −1 at 1.0 A g −1 . The as‐prepared sample exhibits superior cycling performance, whose specific capacity remains 95% at 5.0 A g −1 after 1800 cycles. The excellent performance mainly stems from the synergistic effect of structure modification and heteroatom doping, and the capacitive effects are dictated by kinetical analysis. The synthesized nitrogen and halogen dual‐doped porous graphene is a promising anode material for LIBs. Abstract : According to the Wurtz‐type reaction, nitrogen and halogen dual‐doped porous graphene is synthesized by solvothermal method. The as‐prepared samples are applied as anode for lithium‐ion batteries. Among them, nitrogen and chlorine dual‐doped graphene reveals outstanding performance due to the synergistic effect between doping and porous structure and capacitive effects by kinetical analysis.